083 Novel wireless S – patch device may efficiently detect atrial fibrillation in patients with ischaemic stroke. (29th July 2019) - Lazarovska, Suzana; Tie, Hui; Hopkins, Andrew; Dimitri, Hany; Premawardhana, Upul; Mcdougall, Alan; Gopinath, Sumana; Chow, Josephine; Rajaratnam, Rohan
Abstract : Introduction: Atrial fibrillation (AF) is the most common atrial arrhythmia leading to increased risk of thromboembolic events. Ward telemetry (WT) has a low detection rate for AF in stroke patients and often patients are not appropriately treated with anticoagulation. This study compares conventional 2-day WT versus 4-day wireless S-patch monitoring to detect AF. Methods: Prospective case series. Results: 51 patients admitted for stroke workup were recruited across 2 major tertiary centre's in Sydney to compare WT monitoring for 2 days versus S-patch monitoring for 4 days in the detection of AF. The efficacy to detect AF using both technologies across 76 hours of telemetry was assessed via data extractions and Cardiologist review. A matrix was used to measure nursing/patient satisfaction and setup/resource times were assessed. 84–94% of patients and 75–95% of nursing preferred the S-Patch. Non-parametric tests indicate significant time saving for removal of S-Patch versus WT [2.2 mins vs 5.1 mins (p=0.00)]. Efficacy of S-Patch to detect AF following Cardiologist review was greater than WT, with 7 patients identified with AF by S-Patch versus 1 using WT. The S-patch had a false positive rate of 78%. Conclusion: The S-patch had a higher detection rate of AF compared to WT. This allows patients to be anticoagulated appropriately for the prevention of further stroke. Analysis shows patients and staff overwhelmingly prefer the S-Patch. The S-Patch is sensitive in the detection of AF however it showed a high false positive rate. We are confident that further refinement and advances will provide a novel device in the detection of AF.